Para taekwondo : understanding the perspectives of coaches - Ivček, Karla (Array, 2021)
Sport and physical activity can play significant role in the lives of persons with disabilities. Participating in sports can improve their health and physical capacities, promote constructive use of their time, as well as provide a better way to integrate and be included in the community. The aim of this qualitative study was to gain insight into perspectives of six coaches regarding their work as para taekwondo trainers. The results present the challenges in the coaches’ work, ways of dealing with difficulties related to para taekwondo training, and positive training outcomes. The challenges faced by coaches indicate acceptance of the abilities of the athletes, ascribed incompetence to athletes with disabilities, lack of trust in the abilities of athletes among people in their social environment, and aggressive behaviour exhibited by persons with intellectual disabilities. Other challenges include limited financial resources, the importance of becoming aware of one’s own prejudice about the capabilities of individuals with disabilities, and building relationships with athletes with disabilities. The coaches deal with difficulties related to para taekwondo training by educating themselves and others, applying an individualised approach to training, cooperating with people from the social environment of athletes with disabilities, and considering the work done with athletes with disabilities as a reward. They recognise positive training outcomes for athletes with disabilities through improvements in bodily functioning, better self-image, and further inclusion in the community.